2015
DOI: 10.1111/aor.12586
|View full text |Cite
|
Sign up to set email alerts
|

Tetralogy of Fallot Cardiac Function Evaluation and Intelligent Diagnosis Based on Dual-Source Computed Tomography Cardiac Images

Abstract: Tetralogy of Fallot (TOF) is the most common complex congenital heart disease (CHD) of the cyanotic type. Studies on ventricular functions have received an increasing amount of attention as the development of diagnosis and treatment technology for CHD continues to advance. Reasonable options for imaging examination and accurate assessment of preoperative and postoperative left ventricular functions of TOF patients are important in improving the cure rate of TOF radical operation, therapeutic evaluation, and ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recently, it was shown that the non-physiological high shear stress (NPHSS) environment that occurs with CF-LVADs may be responsible for platelet dysfunction as evidenced by GPIbα, GPVI and GPIIbIIIa receptor shedding. 1416 Understanding of the role of oxidative stress and NPHSS from CF-LVAD as contributory factor in platelet glycoprotein shedding may enable development of effective medical management strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that the non-physiological high shear stress (NPHSS) environment that occurs with CF-LVADs may be responsible for platelet dysfunction as evidenced by GPIbα, GPVI and GPIIbIIIa receptor shedding. 1416 Understanding of the role of oxidative stress and NPHSS from CF-LVAD as contributory factor in platelet glycoprotein shedding may enable development of effective medical management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…13 Studies also revealed that non-physiological high shear stress may also contribute to the shedding of different important platelet receptor glycoproteins. 1416 Several biochemical pathways that induce shedding of GPIbα and/or GPVI have been identified. 1721 While these pathways might be dependent or independent of platelet activation, the loss of these functional receptors may result in defective platelets.…”
Section: Introductionmentioning
confidence: 99%
“…17 Cluster analysis has been used successfully to classify patients with congenital abnormalities into clinically relevant subgroups based on their phenotype, 18 including patient classification based on cardiac imaging. [19][20][21][22] Adequate sample size for cluster analysis was determined considering the number of variables, which may exponentially increase data dimensionality. For this purpose, an approach has been proposed in which meaningful classifications can be obtained using a sample size of 2 × , where x is the number of variables.…”
Section: Discussionmentioning
confidence: 99%
“…NSCT is proposed on the basis of CT and realized through nonsubsampled Laplace pyramid (LP) decomposition and nonsubsampled directional filter banks 29 . Figure 2 shows the structure of NSCT.…”
Section: Methodsmentioning
confidence: 99%